2017
DOI: 10.1177/0260106017748053
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of cardiometabolic health and nutritional status in individuals with positive celiac disease serology

Abstract: Individuals with undiagnosed CD may have unfavorable lipid profiles and be at elevated risk for inadequacy of certain fat-soluble vitamins, but not widespread nutrient deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Long-chain (C20–22) PUFAs are important for optimal metabolism while deficiencies might contribute to the disease onset, including psychiatric diseases and depression that, indeed, are manifestations usually reported by U-CD ( De Palma et al, 2014 ; Jelsness-Jørgensen et al, 2018 ). Impairments in FAs determined by CD were also argued by Jamnik et al (2018) . This research group showed that U-CD had a lower level of circulating HDL-cholesterol and apolipoprotein-A1.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Long-chain (C20–22) PUFAs are important for optimal metabolism while deficiencies might contribute to the disease onset, including psychiatric diseases and depression that, indeed, are manifestations usually reported by U-CD ( De Palma et al, 2014 ; Jelsness-Jørgensen et al, 2018 ). Impairments in FAs determined by CD were also argued by Jamnik et al (2018) . This research group showed that U-CD had a lower level of circulating HDL-cholesterol and apolipoprotein-A1.…”
Section: Discussionmentioning
confidence: 90%
“…The lipidomics based on GC-flame ionization detector (FID) assessed higher ratios of palmitic, palmitoleic, stearic, and oleic acids, as well as lower ratios of linoleic, alpha-linolenic, dihomo-gamma-linolenic, arachidonic, eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids than those of HC. Instead, Jamnik et al (2018) deeply profiled biochemical biomarkers of cardiometabolic health and nutritional status in blood. Compared to those with negative CD serology, U-CD had a lower level of circulating HDL-cholesterol and apolipoprotein-A1.…”
Section: Resultsmentioning
confidence: 99%
“…However, we believe that, in our patient, vitamin C deficiency can be ascribed only to a lack of intake because vitamin C levels are not usually altered in patients affected by celiac disease. 23 No zinc supplementation was started because of the absence of clinical changes related to zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Bile flow rate and the secretion of biliary of its main components, such as cholesterol, phospholipids, and bile acids, were reported to be significantly increased in active CD and be normalized after effective GFD. [ 18 ] This enhanced secretion of newly synthesized and/or absorbed cholesterol directly into the bile has been associated with a decrease in serum cholesterol concentration in CD patients, [ 19 ] which has been observed both in pediatric and adult clinical studies [ 20 , 21 , 22 ]. However, total plasma cholesterol is often associated with a decrease in HDL-cholesterol and, thus, a higher ratio of total cholesterol to HDL-cholesterol, which can also be ameliorated through GFD [ 22 , 23 ].…”
Section: Gallbladder Functioning and Regulation In Celiac Diseasementioning
confidence: 99%